Hadith of Ghadir Khum and the Framing of Shia Teachings: A Comparative Analysis of Panjimas.com and ShiahIndondesia.com from Robert M. Entman’s Perspective - Nur Annisa Istifarin; Muhid Muhid (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2026)
The theological divergence between Sunni and Shia interpretations of the Hadith of Ghadir Khum remains a persistent issue in Islamic discourse, particularly within the digital sphere. This study aims to analyze how two online Islamic media portals, Panjimas.com and ShiahIndonesia.com, frame the Ghadir Khum event and its implications for leadership in Islam. The research applies Robert M. Entman's framing model, encompassing four elements: define problems, diagnose causes, make moral judgment, and treatment recommendation. The findings reveal that Panjimas.com frames the Hadith of Ghadir Khum as a theological misinterpretation by the Shia that requires correction. It emphasizes the term mawla as meaning